A comparative study of the effects of L1 and L2 prewriting discussions on L2 writing performance. (December 2021) - Gao, Jianmin; Min, Shangchao
Abstract: Despite the frequent implementation of prewriting discussion in L2 writing classrooms, little attention has been paid to the issue that which language, L1 or L2, should be used for discussion. To advance our knowledge on this issue, we compared the effects of L1 and L2 prewriting discussions on L2 writing performance. We randomly assigned 66 university students to two groups in terms of the language they were required to use throughout the discussion: the L1 group and the L2 group. Within each group, they formed pairs to talk about a given writing topic, after which they individually finished their writing and completed an online retrospective questionnaire. We compared the writings of the two groups in terms of complexity, accuracy, fluency, content richness, and holistic quality. The results suggested that: 1) the L1 group outperformed the L2 group in lexical complexity, accuracy, and fluency, while there were no between-group differences in other measures; 2) the L1 group overall held more positive views towards the effect of the discussion, especially in terms of the facilitative role of discussion in improving fluency. These findings point to the need of a balanced use of students' L1 and L2 in L2 writing classrooms. Highlights: L1 and L2 prewriting discussions have different effects on L2 individual writing. Using L1 in prewriting discussion can better improve L2 writing quality. Prewriting discussion in L1 is perceived more helpful than in L2.